Diversity and Demographics of Zooarchaeologists: Results from a Digital Survey - Pilaar Birch, Suzanne E. (Ethnobiology Letters, 2015)
Nearly 25 years ago, a “Zooarchaeology Practitioner Survey” was distributed via conventional mail to individuals in the USA and Canada and received 122 responses over a period of several months in 1991. Now, a revised “Demographics in Zooarchaeology Survey” provides an update to those data and assesses the current state of the field. The 2014 survey remained open for 3 months and received 288 responses from practitioners worldwide. Global participation was made possible by hosting the survey online. Key findings of the 1991 survey included disparities in employment rank for women despite similar levels of degree level attainment as men, a point which the 2014 survey sought to investigate. This trend appears to persist for those without the PhD and at the highest levels of income for those holding a PhD. In addition, the recent survey asked participants about their racial or ethnic identity in order to evaluate the demographic diversity of the discipline beyond sex, age, and nationality. Data regarding topical and geographic research area were also collected and reflect a subtle bias towards working with mammals and a focus on research questions grounded in prehistory in Europe and North America, followed by Australia and Southwest Asia. Results are compared with those of the earlier survey and membership information from the International Council for Archaeozoology.